(untitled) (Economics and region, 2025)
The article is devoted to the analysis of the development of political science in the Republic of Poland as an important social science that combines theoretical knowledge of politics with practical influence on the system of public administration. It is shown that the formation of Polish political science took place from interdisciplinary scientific research within the framework of philosophy, history and law to the formation of a separate academic field, which today has a clear institutional structure. The main approaches of Polish researchers to the definition of the concept of «political science» and its relationship with the concepts of «science of politics» and «political science» are highlighted. The educational programs of the leading Polish universities, which ensure the training of specialists according to the standards of the Bologna Process, as well as the implementation of modern methods of policy research, have been analyzed. It has been proven that Polish political science has not only academic, but also applied significance, as it contributes to the modernization of public administration, the professionalization of public administration, the development of political culture and civic participation. Therefore, Polish scientists interpret political science as: a social science that analyzes power, the state, institutions, and the behavior of citizens; a discipline that combines theory (ideas) and empiricism (policy functioning mechanisms); part of the broader field of social or political science, closely related to sociology, law, history, and economics. The diversity and multifacetedness of politics implies the need to distinguish between relevant branches and specializations. Within the framework of political science, the following main fields are distinguished: political theory and the history of political doctrines, political systems, political institutions and international relations. The potential of Polish experience for Ukraine was emphasized, in particular in the field of public authority reform and training of political and administrative personnel. The trend of transition from normative-descriptive to analytical and comparative approaches, integration of political science with economic, sociological and legal sciences has been revealed. It was concluded that modern Polish political science demonstrates a high level of methodological maturity, European integration and practical significance in the system of management decisions, which opens up prospects for the development of comparative studies in the Central-Eastern Europe region.